AN ANALYSIS OF DESCRIPTIVE TEXTS OF READINGPASSAGES IN ENGLISH TEXTBOOKS FOR GRADE SEVENA Systemic Functional Linguistic Perspective - Adisa Dini Anggraem, - (2014)
This study focused on analyzing the Descriptive texts in English textbooks and finding the relevant English textbook to be used as source for teaching and learning Descriptive genre. This study used a descriptive-qualitative method with document analysis technique, using SFL framework analysis. The main data of this study were 10 Descriptive texts from an electronic school book and a printed textbook which have implemented 2013 curriculum. The data analysis was done by examining schematic structure, purpose, linguistic features and meanings presented in texts. The findings showed that in terms of social purpose, all of the Descriptive texts in both textbooks have suited their purpose, describing a specific participant. While in terms of schematic structure, actually all the texts have already had Identification and Description elements, but the distinction between those elements in the Descriptive texts in the electronic school book is not clear. In terms of linguistic features, it is found that some Descriptive texts in the electronic school book do not describe the specific participant in detail and do not use Relational and Material processes frequently, which means that the texts do not achieve criteria of very simple Descriptive text. Moreover, those texts in the electronic school book only consist of three sentences and all of them belong to simplex clauses, so the specific participant in the text is not described in detailed. Thus, it can be derived from the findings that the Descriptive texts in printed English textbook are more sufficient to the criteria of Descriptive text and more relevant to be used as sources in learning Descriptive genre for students, especially tar grade seven students who have already exposed to and learned English in their primary school, meanwhile the Descriptive texts in the electronic school book are more suitable for those students who have not learned English before, because it only consists of three simplex clauses. However, teachers who use electronic school book as their learning source should revise the texts and also provide other additional materials from other sources to enrich the existing Descriptive texts in the electronic school book because those Descriptive texts in electronic school book are very simple and incomplete.